Editorial. (May 2015) - Mansfield-Devine, Steve
Abstract : For all the shock and outrage that greeted the leak of classified documents by Edward Snowden, and the dark secrets of how the US and UK spy on their citizens, it seems as though mass surveillance is here to stay. In fact, it's likely to increase.